Review of the family Ismaridae Thomson, 1858 (Hymenoptera: Diaprioidea) from Iran. (3rd April 2021) - Izadizadeh, Mohammad; Talebi, Ali Asghar; Kolyada, Victor; Farahani, Samira; Kazerani, Farzaneh; Ameri, Ali
ABSTRACT: During our studies on the family Ismaridae, three species from northern Iran were identified and illustrated: Ismarus dorsiger (Haliday, 1831), Ismarus halidayi Förster, 1850 and Ismarus rugulosus Förster, 1850. The first two species are new records for Iran. Diagnostic characters for all three species are provided along with illustrations. A key to the Iranian species of the genus Ismarus, as well as a distribution map of the recorded species throughout the world, is presented.